First Report on Large-Scale Phaeocystis globosa Bloom in the Southern Yellow Sea, China - Li, Dongmei; Xue, Yue; Song, Qingshang; Cui, Fuxu; Ma, Yujuan; Tong, Mengmeng; Shen, Pingping (Frontiers in Marine Science, 2022)
From late November 2021, a large-scale Phaeocystis globosa bloom occurred for the first time in the southern Yellow Sea, covering an area of over 630 km2 and lasting for nearly 40 days. Two investigations, combined with satellite remote sensing, were successively conducted on December 11 and 23, 2021 to study the bloom dynamics and impacts. During the bloom, the average temperature decreased from 11.8°C to 10.0°C and salinity increased slightly from 30.9 to 31.3. The pH remained consistently at 8.22, while dissolved oxygen and chlorophyll-a content decreased dramatically from 7.23 mg L-1 to 5.82 mg L-1, 8.72 μg L-1 to 2.35 μg L-1, respectively. The concentration of nitrate and silicate decreased moderately, whereas nitrite, ammonium and phosphate increased obviously, especially the ammonium content, elevated from 0.90 μmol L-1 to 1.39 μmol L-1 during two investigations. Meanwhile, the P. globosa colony densities varied between 10 colonies L-1 and 185 colonies L-1, with a mean of 70.0 colonies L-1 on Dec. 11, and decreased dramatically to an average of 1.46 colonies L-1 on Dec. 23. Similarly, single cells decreased from 3.6×106 cells L-1 to 1.05×106 cells L-1 accordingly. Moreover, diameter of the colonies varied from 0.5 cm to 2.0 cm, with an average diameter of 1.0 cm, and no colonies smaller than 0.5 cm was observed in the bloom. Correlation analysis indicated temperature and salinity related with the colony abundance positively (P<0.001) and negatively (P<0.05), respectively, and silicate and nitrite concentration showed significant positive effects on solitary cell density (P<0.05). No mortality of marine organisms was observed and the haemolytic activity of Phaeocystis samples was low, varying between 13.07 Hu L-1 and 19.22 Hu L-1. Based on phylogenetic analysis, this P. globosa strain may represent a possible different ecotype which prefers low temperature and is less or nontoxicity.